2019
DOI: 10.1111/1365-2435.13452
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that phosphorus fertilization and arbuscular mycorrhizal symbiosis can reduce the carbon cost of phosphorus uptake

Abstract: Plants allocate substantial amounts of carbon (C) below‐ground to obtain nutrients and other resources. Increasing nutrient availability typically reduces the C investment in root growth and mycorrhizal fungi, hence reducing the C cost of nutrient acquisition. This C cost of nutrient acquisition, however, remains poorly quantified. In a P fertilization experiment with Zea mays, we examined below‐ground C allocation and the C cost of phosphorus (P) uptake. In addition, we compared plants inoculated with arbuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 66 publications
4
27
0
Order By: Relevance
“…The main hypothesis that BPE increases with increasing P fertilization was refuted, and while R aut :GPP was expected to be relatively constant among treatments, we found an increase with increasing P fertilization due to increased C partitioning to aboveground respiration. The difference between pasteurized (no AMF) and AMF‐inoculated treatments, together with the comparison with a previous experiment in a similar set‐up, suggest a role for AMF in determining these C partitioning patterns; as suggested by Ven et al (2019), AMF can reduce the C cost of P uptake, even when their abundance and hence their C use is low. Our results emphasize the need to take into account not only nutrient availability, but also mycorrhizal symbionts when studying and modelling C partitioning in terrestrial ecosystems.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The main hypothesis that BPE increases with increasing P fertilization was refuted, and while R aut :GPP was expected to be relatively constant among treatments, we found an increase with increasing P fertilization due to increased C partitioning to aboveground respiration. The difference between pasteurized (no AMF) and AMF‐inoculated treatments, together with the comparison with a previous experiment in a similar set‐up, suggest a role for AMF in determining these C partitioning patterns; as suggested by Ven et al (2019), AMF can reduce the C cost of P uptake, even when their abundance and hence their C use is low. Our results emphasize the need to take into account not only nutrient availability, but also mycorrhizal symbionts when studying and modelling C partitioning in terrestrial ecosystems.…”
Section: Discussionsupporting
confidence: 62%
“…SE of the mean was calculated by error propagation. As previously described in Ven, Verlinden, Verbruggen, and Vicca (2019), we calculated rhizosphere respiration (R rhizo ) using the Picarro CO 2 effluxes and associated δ 13 C from the two collars installed in each mesocosm, to estimate total R rhizo (∑R rhizo ) over the entire growing season (see Appendix S4). SE of ∑R rhizo was calculated by error propagation.…”
Section: Methodsmentioning
confidence: 99%
“…Because arbuscular mycorrhizal fungi take up to 20% of assimilated C from the host plant (Konvalinková et al, 2017), and since geophytes function under an efficient system of resource allocation by having to partition carbon fixed through photosynthetic activity between symbiont, host metabolic activity and storage organ, it was suggested that geophytes might be more sensitive to carbon expenditure (Crișan et al, 2018). Below-ground C partitioning by the plant is expected to vary during growing season (Ven et al, 2019), but the role played by AM in C allocation by the host according to phenophase could hold the keys to better understanding in-plant C dynamics, particularly in geophytes. And for this reason, it is proposed that geophytes might be suitable model plants for the study of these mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Ven et al. (2019) found, for example, that AM fungi stimulated plant growth and increased the total belowground carbon flux in an experiment with maize plants. Burghelea et al (2018) even suggested that AM fungi can enhance root exudation especially in substrates that are difficult to weather.…”
Section: The Importance Of Mycorrhizal Fungi In "Enhanced Weathering"mentioning
confidence: 99%
“…of silicate minerals(Dontsova et al, 2020). AM fungi can have a strong effect on these belowground plant processes Ven et al (2019). found, for example, that AM fungi stimulated plant growth and increased the total belowground carbon flux in an experiment with maize plants Burghelea et al (2018).…”
mentioning
confidence: 99%